From cereus to anthrax and back again: Assessment of the temperature-dependent phenotypic switching in the “cross-over” strain Bacillus cereus G9241 - Manoharan, Shathviga; Taylor-Joyce, Grace; Brooker, Thomas A.; Hernández Rodríguez, Carmen Sara; Hapeshi, Alexia; Baldwin, Victoria; Baillie, Les; Oyston, Petra C. F.; Waterfield, Nicholas R. (Frontiers in Microbiology, 2023)
Bacillus cereus G9241 was isolated from a Louisiana welder suffering from an anthrax-like infection. The organism carries two transcriptional regulators that have previously been proposed to be incompatible with each other in Bacillus anthracis: the pleiotropic transcriptional regulator PlcR found in most members of the Bacillus cereus group but truncated in all B. anthracis isolates, and the anthrax toxin regulator AtxA found in all B. anthracis strains and a few B. cereus sensu stricto strains. Here we report cytotoxic and haemolytic activity of cell free B. cereus G9241 culture supernatants cultured at 25 °C to various eukaryotic cells. However, this is not observed at the mammalian infection relevant temperature 37 °C, behaving much like the supernatants generated by B. anthracis. Using a combination of genetic and proteomic approaches to understand this unique phenotype, we identified several PlcR-regulated toxins to be secreted highly at 25 °C compared to 37 °C. Furthermore, results suggest that differential expression of the protease involved in processing the PlcR quorum sensing activator molecule PapR appears to be the limiting step for the production of PlcR-regulated toxins at 37 °C, giving rise to the temperature-dependent haemolytic and cytotoxic activity of the culture supernatants. This study provides an insight on how B. cereus G9241 is able to ‘switch’ between B. cereus and B. anthracis–like phenotypes in a temperature-dependent manner, potentially accommodating the activities of both PlcR and AtxA.